Perancangan Video Company Profile Sebagai Penunjang Informasi Pada SMK Kartika X – 1 - Po Abas Sunarya; Sandro Alfeno; Lola Sartika (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2021)
In today's modern era, online information technology is widely used by companies or other institutions to convey information and serve as promotional tools, using audio-visual media with a 2-dimensional animation-based method that is able to attract audiences. To get this information, you can access it in various social media. SMK Kartika X-1 West Jakarta is a private vocational education institution that still uses printed media such as benner, brochures, banners in the form of images and text as information media. However, using this print media to provide information is less effective because of its less extensive reach. Based on the above problems, a study is needed to design a video company profile to complement the school's information media.This research uses methods such as: problem analysis, data collection, SWOT analysis, media production concept (KPM). The design of this video is assisted by editor software such as Adobe Illustrator (Ai), Adobe After Effects (Ae) and Adobe Premiere Pro (Pr). This information video will be implemented through YouTube and social media of the Official SMK Kartika X-1. With this video company profile it can help this school in introducing the school profile.